The influence of internet use on identity in Asia: a social psychological approach - Dell, Peter (Curtin University of Technology, 2006)
George Herbert Mead suggested that identity is constructed rather than fixed, a notion taken up by Erving Goffman in his detailed analysis of social interaction (Goffman, 1059). Goffman described social behaviour using a theatrical metaphor in which roles are performed for an audience. Role descriptions describe how to behave and interact; it is the detail of such descriptions that is socially negotiated during identity construction. This construction can be considered as a tension between internal and external forces.Not all identities are equally malleable during the identity construction process; those identities strongly influenced by internalised norms and values, or by embodiment, are resistant to change (although change is not impossible). Others, such as professional identity, are much more flexible.A considerable portion of the literature relating to identity online examines gender, yet gender is one of the more change-resistant aspects of identity. However there are many other aspects to identity that are more likely to be influenced by the different social interactions to which Internet-use exposes us.This paper uses interview data from university students from a number of Asian countries to explore which aspects of their identities are most influenced by social interactions made possible by the Internet. The findings suggest that identity construction is indeed influenced by Internet use, although not necessarily in a uniform way.